PRICKLY PEAR (OPUNTIA FICUS INDICA L.) CACTUS AS A SOURCE OF VITAMIN A - TELES, FRANCISCO FRANCO FEITOSA; WHITING, FRANK M.; PRINCE, RALPH L.; BROWN, WILLIAM H.; REID, BOBBY L.; WEGNER, THOMAS N.; RENUNCIO, ELIANA (Revista Ceres, 2015)
.